Proximity and economic activity: An analysis of vendor‐university transactions. (22nd June 2018) - Goldschlag, Nathan; Lane, Julia; Weinberg, Bruce A.; Zolas, Nikolas
Abstract: This paper uses transaction‐based data to provide new insights into the link between the geographic proximity of businesses and associated economic activity. It develops two new measures of, and a set of stylized facts about, the distances between observed transactions between customers and vendors for a research intensive sector. Spending on research inputs is more likely with businesses physically closer to universities than those further away. Firms supplying a university project in one year are more likely to subsequently open an establishment near that university. Vendors who have supplied a project, are subsequently more likely to be a vendor on the same or related project.